THE THEORY AND APPLICATION OF REGRESSION ANALYSIS AND THE LEAST-SQAURES PRINCIPLE - De Viliers, P. (Scientia Militaria - South African Journal of Military Studies, 2012)
The theory and practice of regression analysis, and the principle of least-squares on which it is based, is frequently encountered in Mathematics and particularly Statistical Mathematics, but less well known are some very useful applications in a military environment. It is therefore the aim of this article to firstly give a general description of the theory of regression analyses, and secondly to highlight some military applications of the theory.